Studies on the Cancionero de Baena - Fraker, Charles F. (Book collections on Project MUSE., 1966)
In this study, Dr. Charles F. Fraker presents the first formal study of Jewish influences in the famous fifteenth-century cancionero, composed at the court of the poet-king, John II of Castile. In particular, the four studies in this work seek to highlight the permanence of ideas amongst the works of poets known or hypothesized to be conversos. This book opens a bright new chapter in the study of Jewish history in Spain.